2014
DOI: 10.3109/14397595.2014.979523
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confocal scanning laser microscopy in patients with primary Sjögren's syndrome: A monocentric experience

Abstract: CSLM might be a useful novel tool in the assessment of the involvement of the lachrymal functional unit in pSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In terms of corneal subbasal nerve morphology, controversial results have been demonstrated in several studies among different DED types [ 12 15 ]. Previous study investigated the corneal nerve morphology of SSDE concluded that SSDE has more corneal nerve density and number than non-Sjögren dry eye disease (NSDE) in China, which is contrary to studies in western populations [ 13 , 15 ]. The purpose of this study was therefore to investigate the morphology of corneal subbasal nerves and its relationship with clinical parameters in patients with primary SSDE and NSDE based on a Chinese population.…”
Section: Introductionmentioning
confidence: 86%
“…In terms of corneal subbasal nerve morphology, controversial results have been demonstrated in several studies among different DED types [ 12 15 ]. Previous study investigated the corneal nerve morphology of SSDE concluded that SSDE has more corneal nerve density and number than non-Sjögren dry eye disease (NSDE) in China, which is contrary to studies in western populations [ 13 , 15 ]. The purpose of this study was therefore to investigate the morphology of corneal subbasal nerves and its relationship with clinical parameters in patients with primary SSDE and NSDE based on a Chinese population.…”
Section: Introductionmentioning
confidence: 86%
“…Twelve studies used either the SSCM or LSCM to examine sub‐basal nerves in patients with DED related to SS 24,25,27‐36 . Six of these studies compared nerve fibre number and morphology of individuals with SS‐associated DED to non‐Sjögren's‐associated DED (non‐SS) and healthy controls.…”
Section: Corneal Nervesmentioning
confidence: 99%
“…In fact, in vivo confocal microscopy has demonstrated corneal nerve alterations in the setting of corneal surgery [70] and Sjögren’s syndrome (a condition in which chronic corneal staining is a hallmark) [71]. Electrophysiologically, peripheral corneal nerves have been found to sensitize when subjected to an inflammatory milieu and after lacrimal gland transection [72, 73].…”
Section: Shared Neurophysiological Abnormalities Between Ocular Drynementioning
confidence: 99%